Factors Associated with the Incidence of COVID-19: A Case Control Study in Tasikmalaya, Indonesia - Zahra Nurlaelasari; Wuri Ratna Hidayani (The Indonesian Institute of Science and Technology Research, 2023)
This case-control study aimed to investigate the relationship between smoking habits, electronic cigarette use, vaccination status, comorbidities, and the incidence of COVID-19. A total of 63 participants, including 21 cases and 42 controls, were included based on specific criteria. Data were collected through a questionnaire and analyzed using univariate and bivariate analyses. The results revealed that there was no significant association between smoking habits (p value= 0.287), e-cigarette use (p value= 0.114), and vaccination status (p value= 0.287) with the incidence. However, a significant relationship was observed between comorbidities and the incidence (p value= 0.000). These findings suggest that while smoking habits, e-cigarette use, and vaccination status may not be significantly associated with the incidence, comorbidities play a significant role. Further research and public health efforts are needed to explore preventive strategies and support individuals with comorbidities in reducing their susceptibility to COVID-19.